2009
DOI: 10.1002/sce.20368
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning up and down a food chain: Using an assessment framework to investigate students' middle knowledge

Abstract: Being able to make claims about what students know and can do in science involves gathering systematic evidence of students' knowledge and abilities. This paper describes an assessment system designed to elicit information from students at many placements along developmental trajectories and demonstrates how this system was used to gather principled evidence of how students reason about food web and food chain disturbances. Specifically, this assessment system was designed to gather information about students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 27 publications
(32 reference statements)
3
83
0
5
Order By: Relevance
“…In contrast, a misconceptions [7] or knowledge-in-pieces (resources) [8,9] perspective treats students' knowledge as more fragmented and, in the latter case, more context-dependent. These two perspectives are consistent with evidence suggesting that student thinking in the "messy middle" [10] of LPs may be particularly fragmented and context-dependent [11]. A pilot study of one physics teacher's interactions with LP-based score reports [12] revealed that he expressed all three views of student thinking, switching between reasoning about student ideas in terms of LP levels and finer-grained knowledge elements.…”
Section: Introductionsupporting
confidence: 78%
“…In contrast, a misconceptions [7] or knowledge-in-pieces (resources) [8,9] perspective treats students' knowledge as more fragmented and, in the latter case, more context-dependent. These two perspectives are consistent with evidence suggesting that student thinking in the "messy middle" [10] of LPs may be particularly fragmented and context-dependent [11]. A pilot study of one physics teacher's interactions with LP-based score reports [12] revealed that he expressed all three views of student thinking, switching between reasoning about student ideas in terms of LP levels and finer-grained knowledge elements.…”
Section: Introductionsupporting
confidence: 78%
“…When students' comments started to discuss the quality of argumentation, students also took it to the next level by discussing the role of content in the assignments and group comments. This is also an important finding since, Gotwals and Songer (2010) underlined that the quality of the arguments is strongly related with content understanding.…”
Section: Discussionmentioning
confidence: 60%
“…Bir dengesizlik durumunun ardından, denge yeniden kurulmaktadır (Sanders vd., 2006). Benzer şekilde, bazı öğrenciler; ekosistemin öğelerindeki herhangi bir değişikliğin tüm sistemi etkileyeceğini kavrayamamakta ve ekosistemdeki canlıların, meydana gelecek değişimden ancak aralarında bir besin zinciri ilişkisi varsa etkileneceğine inanmaktadırlar (Arkwringhti 2014; Gotwals ve Songer, 2010;Grotzer, 2009;Munson, 1994). Gotwals ve Songer (2010)'in çalışmalarına katılan bazı altıncı sınıf öğrencileri, meydana gelebilecek bir bozulmanın ekosistem üzerindeki etkilerinin neler olabileceği açıklamakta güçlük yaşamışlardır.…”
unclassified
“…Benzer şekilde, bazı öğrenciler; ekosistemin öğelerindeki herhangi bir değişikliğin tüm sistemi etkileyeceğini kavrayamamakta ve ekosistemdeki canlıların, meydana gelecek değişimden ancak aralarında bir besin zinciri ilişkisi varsa etkileneceğine inanmaktadırlar (Arkwringhti 2014; Gotwals ve Songer, 2010;Grotzer, 2009;Munson, 1994). Gotwals ve Songer (2010)'in çalışmalarına katılan bazı altıncı sınıf öğrencileri, meydana gelebilecek bir bozulmanın ekosistem üzerindeki etkilerinin neler olabileceği açıklamakta güçlük yaşamışlardır. Hogan (2000)'ın çalışmasına göre ise; öğrenciler bir ekosistemdeki kirleticilerin, sadece organizmayla doğrudan teması olduğu durumlarda etkili olduğunu düşünürken, organizma üzerindeki dolaylı etkilerini düşünememişlerdir.…”
unclassified
See 1 more Smart Citation